2019 27th European Signal Processing Conference (EUSIPCO) 2019
DOI: 10.23919/eusipco.2019.8902559
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for Piecewise Constant Signal Approximations

Abstract: We consider the problem of finding optimal piecewise constant approximations of one-dimensional signals. These approximations should consist of a specified number of segments (samples) and minimise the mean squared error to the original signal. We formalise this goal as a discrete nonconvex optimisation problem, for which we study two algorithms. First we reformulate a recent adaptive sampling method by Dar and Bruckstein in a compact and transparent way. This allows us to analyse its limitations when it comes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…-Polygonal finite elements [20,53] -Stochastic hill climbing [52] -Optimal control approaches [19,37] -Particle swarm optimisation [12,13] Table 1: Taxonomy of Spatial Data Optimisation Algorithms…”
Section: Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…-Polygonal finite elements [20,53] -Stochastic hill climbing [52] -Optimal control approaches [19,37] -Particle swarm optimisation [12,13] Table 1: Taxonomy of Spatial Data Optimisation Algorithms…”
Section: Improvementmentioning
confidence: 99%
“…Finally, the method by Dar and Bruckstein (2019) [24] finds an optimised mask for piecewise constant approximations of 1D signals. This approach has three key assumptions: smoothness of the input signal f , local linearity of f , and a balanced error distribution over the mask pixels P (Bergerhoff et al, 2019; Dar and Bruckstein, 2019) [13,24].…”
Section: Analytic Mask Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Unconstrained mask approaches: While there are numerous publications that deal with optimal selection of sparse known data for inpainting [4,[11][12][13][14][42][43][44][45][46][47] , only few use them for actual compression. Hoffman et al [29] primarily use a regular grid as already mentioned, but it also uses some unconstrained mask points to further enhance quality which are encoded using JBIG .…”
Section: Related Workmentioning
confidence: 99%
“…This can be seen from the pattern that has not decreased from year to year in the last 18 years. Studies related to signal modeling with PC models can be found in various kinds of literature, for example [5][6][7]. Based on the type of noise, some PC models also use different types of noise, for example, Gaussian [8], Poisson [9], Gamma [10], and Rayleigh [11].…”
Section: Introductionmentioning
confidence: 99%